Checklist of the ants of Slovenia (Hymenoptera: Formicidae) - Gregor Bračko (Natura Sloveniae)
A checklist of the ants of Slovenia with 132 species is presented. Sixteen species are new for the Slovenian ant fauna (Ponera testacea, Cardiocondyla elegans, Myrmica gallienii, Myrmica lobulicornis, Myrmica rugulosa, Temnothorax italicus, Temnothorax lichtensteini, Temnothorax recedens, Temnothorax saxonicus, Tetramorium hungaricum, Tetramorium moravicum, Tetramorium semilaeve, Formica fuscocinerea, Lasius balcanicus, Plagiolepis ampeloni, Plagiolepis xene). Distribution of the recorded species according to the phytogeographic regions of Slovenia is also indicated.